Analysis of translatomic changes in the Ubqln2P497S model of ALS reveals that motor neurons express muscle-associated genes in non-disease states - Stansberry, Wesley M.; Fiur, Natalie C.; Robins, Melissa M.; Pierchala, Brian A. (Frontiers in Neurology, 2024)
IntroductionAmyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease characterized by progressively worsening motor symptoms that lead to eventual fatal paralysis. The number of gene mutations associated with ALS have increased dramatically in recent years, suggesting heterogeneity in the etiology of ALS and the need to develop new models of the disease that encompass these pathologies. In 2011, mutations in the UBQLN2 gene were identified in families with both ALS and frontotemporal dementia (FTD) and have since been linked to ubiquitinated TDP43 inclusion pathology. The involvement of UBQLN2 in ubiquitination and proteasome function suggests an important role in proteostasis, which is reported to be impaired in ALS.MethodsA UBQLN2 mouse model was generated for the P497S mutation and recapitulates some of the motor symptoms of ALS. We utilized ribosomal profiling followed by mRNA sequencing of associated transcripts to characterize gene expression changes of motor neurons in the Ubqln2P497S model and evaluated ALS phenotypes in these animals.ResultsAt 12 months of age, we observed reduced motor neuron survival and neuromuscular junction denervation in these mice that translated into motor deficits observed in locomotor behavioral trials. The sequencing of motor neuron transcripts revealed that Wnt pathways and muscle-related transcripts were downregulated in Ubqln2P497S mice, while metabolic pathways were upregulated.DiscussionSurprisingly, genes often reported to be muscle-specific, such as Desmin and Acta1, were expressed in motor neurons and were dramatically downregulated in symptomatic Ubqln2P497S mice. The expression of muscle transcripts by motor neurons suggests their potentially supportive role in skeletal muscle maintenance.